Foreign Direct Investment in Multi-Brand Retail: Opportunities and Threats - Kumar, Sunil (Indian Journal of Marketing, 2012)
In the era of liberalization, globalization and privatization, the whole economy is opening up gradually. The Indian retail sector has also not remained untouched. India has already allowed 51 percent FDI in single-brand retail, and 100 percent FDI in cash-and-carry or wholesale trading and now, there is a proposal by the Department of Industrial Policy and Promotion (DIPP) to allow 51 percent FDI in multi-brand retailing (Hindustan Times, 30th August, 2010). India has 15 million-plus retailers who account for 350 plus billion of annual sales. The retail space is dominated by the unorganized sector that contributes to 94 percent of the sales. The retail sector is the largest sector in India after agriculture, accounting for over 10 percent of the countryâ€™s GDP and around 8 percent of the employment. India has the most unorganized retail market in the worldthe largest sector in India after agriculture, accounting for over 10 percent of the country’s GDP and around 8 percent of the employment. India has the most unorganized retail market in the world (DIPP, 2010). Most retailers of the unorganized retail market have their shops in the front or at the back of the houses. The Indian retail sector is one of the fast-growing sectors, with several players entering the market. Currently, the organized sector accounts for only 2 percent, indicating a huge potential market opportunity.